Catastrophe Risk and Reinsurance : A Country Risk Management Perspective (The World Bank, 2004)
This compact but comprehensive exposé of the best international practical experience in catastrophe risk management at the country level outlines the key challenges involved in building national catastrophe insurance schemes. Clearly illustrates how countries exposed to natural disasters can manage their catastrophe risk exposures to reduce the cost of risk for national economies by following the classical corporate risk management model. Contains valuable practical insights for risk and insurance professionals, and government policy makers on the key challenges involved in designing a successful national catastrophe risk management programme. Offers innovative insights of the foremost academics in the area alongside practical expertise from leading international reinsurance and risk professionals, based on their experience of running some of the largest catastrophe risk programmes worldwide. Demonstrates the importance of public-private partnerships in catastrophe risk financing by suggesting the roles of government and private risk markets. In addition to risk financing, this title uniquely covers the role of risk reduction and prevention in disaster prone countries. Examines the best international practices at each stage of catastrophe risk management including: country risk assessments and risk modelling, risk transfer products as well as optimal institutional arrangements for national catastrophe risk management, including national reinsurance and insurance pools